EFFECT OF CORTISONE ON GENETIC RESISTANCE TO MOUSE HEPATITIS VIRUS IN VIVO AND IN VITRO - Ruth Gallily; Anne B. Warwick; Frederik B. Bang (1964)
Mutations are important because they provide raw material for evolution. Some types of mutations occur more often than others, and the strength of such mutational bias varies across species. It is not clear how this variation arises. We ...Biased mutation spectra are pervasive, with wide variation in the magnitude of mutational biases that influence genome evolution and adaptation. How do such diverse biases evolve? Our experiments show that changing the mutation spectrum allows populations ...